A Mou Zongsan's criticism of Xunzi: 'Morality is external'. Issue 1 (2nd January 2023) - Bedel, Burcin
ABSTRACT: Xunzi lived at the end of the Warring States period (480/403–222 B.C.) of China. He sought solutions to the problems of social and political life, and the management theories he put forward constituted his primary system of thoughts. Xunzi saw a connection between politics and morality and embodied this connection with the concept of rituals . Unlike the thinkers, such as Confucius and Mengzi, who found the basis of morality in Tian 天 (nature), Xunzi brought a new interpretation to the creation process of rituals and morality within the framework of conscious activity . This paper focuses on the creation of rituals and the basis of morality. It interprets Mou Zongsan's criticism of Xunzi: 'morality is external'. By showing the relationship between human nature, Tian, and rituals, I will argue whether morality is 'internal' or 'external' to humans in Xunzi's thoughts.